Effect of dietary restraint and mood state on attentional processing of food cues. (March 2019) - Donofry, Shannon D.; van Zoest, Wieske; Moonen, Andrea; Sacchetti, Sofia; Nederkoorn, Chantal; Roefs, Anne
Abstract: Background and objectives: Research linking dietary restraint to attentional bias toward food cues has been equivocal, suggesting that dietary restraint may only influence attentional processing of food in certain contexts. The present study examined whether negative mood strengthens the association between dietary restraint and attention bias for food. Methods: Healthy female participants were randomized to either a neutral ( n  = 47) or negative mood ( n  = 49) induction. Participants then completed a visual search task featuring targets displayed adjacent to pictures of palatable food, musical instruments, or non-instrument filler objects. Attention bias for food was operationalized as shorter response latency when the target appeared adjacent to palatable food as compared to musical instruments. Attention bias was examined in a 2 (mood condition) × 2 (picture: food vs. instrument) × 2 (target location: match vs. mismatch) repeated measures ANCOVA, with dietary restraint as a continuous covariate and response latency as the dependent variable. Results: Though there was no evidence of an interaction between mood condition and dietary restraint, mood had an influence on attention allocation. Contrary to study hypotheses, individuals in the neutral mood condition, but not those in the negative mood condition, responded in a manner indicative of bias toward food. Limitations: Additional research is necessary to validate the experimental task used in the present study to assess food-specific attentional bias. Conclusions: Neutral mood may be associated with enhanced processing of palatable food cues. Critically, results do not support the hypothesized link between negative mood and attention bias for food. Highlights: Research linking dietary restraint to attentional bias for food has been inconsistent. Contextual factors like negative mood may enhance attentional bias for food. We examined the effect of induced negative mood on attentional processing of food cues. Dietary restraint was not associated with attentional bias for food. Neutral but not negative mood predicted better performance on food trials.